Dança inclusiva e deficiência intelectual: um estudo com educandos da rede municipal de ensino de Aparecida de Goiânia - Cunha, Gisele Bizerra da (2017)
The motivation and the interest that led to this research study are the results of experiences as a researcher with dance for people with intellectual disabilities at the Association - Associação Pestalozzi de Goiânia – CAE Peter Pan. Having noticed the importance that dance had in the life of these students with intellectual disabilities and how they showed pleasure and interest in this activity, it became necessary to study and analyse dance and how it could contribute to the inclusion of these students in school and society. The present research seeks, therefore, a dialogue between dance and inclusion and presents the following question for investigation: How can dance contribute to the inclusion of students with intellectual disabilities in the years of basic education? The main goal is to verify how dance makes inclusion possible within the context of basic education. The research is qualitative and class observations and interviews were undertaken at two fulltime municipal schools (Escolas Municipais de Ensino Integral) in the municipality of Aparecida de Goiânia. Authors that deal with the body, dance, inclusive education, multiple intelligences and inclusive dance form the theoretical base. Regarding inclusive education in Brazil and in Aparecida de Goiânia the works of Monteiro (2001), Sassaki (1998), and Santos (2016) were studied as well as pertinent national and municipal documents. For the theme of intellectual disability, Almeida (2012), Cintra (2002), and Matos (2012) formed the theoretical base. Gardner (1995) and Smole (1999).were researched for the theme of multiple intelligences. For the theme of dance, we based our research on Fahlbusch (1990), Marques (2010), Laban (1990), and Scarpato (2001). In regards to inclusive dance, we studied Cintra (1992), Figueiredo (1997, 1999), Ramos (2010), Tolocka and Verlengia (2006). Considering the data that was generated and analysed in this research study, it is possible to conclude that the practice of inclusive dance in school can contribute significantly in terms of affective, social, motor and cognitive development to students with intellectual disabilities, allowing these students with this type of disability to feel included in the school setting and in society. It was also possible to conclude that a type of education that takes into account the theory of multiple intelligences can contribute to the process of inclusion in school.